2005
DOI: 10.2113/gscanmin.43.6.2049
|View full text |Cite
|
Sign up to set email alerts
|

Carbonatites and Carbonatites and Carbonatites

Abstract: Carbonatites are redefined using a mineralogical-genetic classification and divided into two groups: primary carbonatites, and carbothermal residua. Attention is drawn to the fact that carbonatite is both a petrographic term applicable to a particular rocktype as well as a group name applied to a complex of related carbonate and silicate rocks in a magmatic or extrusive complex. Primary carbonatites, in terms of mineralogical-genetic classifications, rather than simple modal classifications, can be divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(163 citation statements)
references
References 71 publications
5
146
1
11
Order By: Relevance
“…Carbonatites are also considered primary mantle melts generated through partial melting of CO 2 -bearing peridotite [15][16][17][18][19]. They are subdivided into primary magmatic carbonatites and carbothermal residual carbonatites formed from low temperature fluids that are rich in CO 2 , H 2 O and fluorine [20]. Although carbonatite magmas have formed from primary melts or as immiscible melt fractions of CO 2 -saturated silicate melt, the associated RE carbonatite are considered to be a late 'magmatic' to 'hydrothermal' event [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonatites are also considered primary mantle melts generated through partial melting of CO 2 -bearing peridotite [15][16][17][18][19]. They are subdivided into primary magmatic carbonatites and carbothermal residual carbonatites formed from low temperature fluids that are rich in CO 2 , H 2 O and fluorine [20]. Although carbonatite magmas have formed from primary melts or as immiscible melt fractions of CO 2 -saturated silicate melt, the associated RE carbonatite are considered to be a late 'magmatic' to 'hydrothermal' event [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The carbonatites at Laughlin Peak and in Mexico are best described as carbonatites associated with potassic and sodic plutonic rocks [203]. This type of carbonatites typically represents low-temperature, low-pressure, fractional-crystallization derivatives of diverse alkaline parental magmas derived from metasomatized lithospheric mantle [203][204][205]. Thus, both upper mantle and lower to upper crustal source rocks are involved in forming GPM deposits, which is supported by the geochemical and isotopic evidence (Tables 1 and 4).…”
Section: Origin Of Gpm Depositsmentioning
confidence: 73%
“…Most identified carbonatites are intrusive bodies, but a few extrusive examples are known, including the active Oldoinyo Lengai carbonatite volcano in northern Tanzania (Van Straaten, 1989). Carbonatites can be quite diverse and likely originate from multiple processes (Woolley, 2003;Mitchell, 2005). Alkaline intrusive rocks tend to be spatially associated with carbonatites and contain elevated concentrations of REEs; thus, we chose to treat these two subclasses of alkaline rocks together.…”
Section: Alkaline Igneous Rocksmentioning
confidence: 99%
“…Field data, experimental petrology, stable and radiogenic isotopic systematics, trace element geochemistry, and evaluation of mantle xenoliths provide insight into the nature of the initial melts and their possible evolutionary paths. Mitchell (2005) stressed that not all carbonatites are alike and suggested that the chemical variations of carbonatites could be the result of different mantlesource characteristics. Current models for the generation of carbonatites have been summarized in recent reviews by Le Bas (1987), Gittins (1989), Bailey (1993), andWinter (2001).…”
Section: Carbonatite Intrusionsmentioning
confidence: 99%